Aluminum Doping Effects on Large LiNi0.8Co0.1Mn0.1O2 Single Crystal Particles Prepared in a Molten LiOH-Li2SO4 Flux. Issue 2 (28th February 2023) - Takamori, Syunya; Doi, Takayuki; Inaba, Minoru
Abstract : Large-size single crystal LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) particles of ∼5 μ m in size were prepared in a LiOH-Li2 SO4 molten flux using a temperature-swing technique from 1000 to 780 °C. The resulting single crystal particles showed good cycleability though the initial capacity was low.It was found that Al ion (ca. 10%) was unexpectedly incorporated within the lattice of the single crystal particles from an alumina boat, which stabilized the layered structure and gave good cycleability.The doping level of the Al ion was optimized, and 2.8% Al doped NCM811 particles delivered the highest initial capacity of 174 mAh g −1 with good cycleability up to the 50th cycle.In addition, Al doping improved the rate-capability of NCM811 single crystal particles.The rate-capability of 2.8% Al doped NCM811 particles was comparable with that of the conventional polycrystalline NCM811.